2013
DOI: 10.1002/14651858.cd008300.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Treating BCG-induced disease in children

Abstract: Treating BCG-induced disease in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
1
8

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 35 publications
2
71
1
8
Order By: Relevance
“…Cuello-Garcia et al found isoniazid injection after aspiration may be useful, but there are limited data in literature [5]. In our study, oral isoniazid and rifampicin treatments were given to six (30%) patients.…”
Section: Bcg Vaccine Complicationsmentioning
confidence: 70%
See 3 more Smart Citations
“…Cuello-Garcia et al found isoniazid injection after aspiration may be useful, but there are limited data in literature [5]. In our study, oral isoniazid and rifampicin treatments were given to six (30%) patients.…”
Section: Bcg Vaccine Complicationsmentioning
confidence: 70%
“…Several complications have been reported after the routine immunization program of BCG vaccine. Although some of these are normal vaccine reactions, unexpected complications have been noted [3][4][5][6][7][8][9]. Adverse reactions may be affected with some factors like patient's age, vaccine strains, dosage, erroneous administration, and disturbance of cellular immunity [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8] Our patient affected with T-B+ SCID presented a localized infection at the site of inoculum and satellite lymph node, a consequence of BCG infection that became disseminated during pre-engraftment bone marrow aplasia induced by allo-HSCT conditioning regimen, despite 4 months of previous, presumptively effective anti-BCG therapy with isoniazid, rifampin and ethambutol. [9][10][11] This dissemination was finally controlled by this combination of antibiotics, with temporary addition of amikacin (3 months) and levofloxacin (6 months) 11,12 in the early postengraftment period, and immune reconstitution (despite immunosuppression for management of GvHD). A comprehensive Medline search using the keywords 'cutaneous complication' and 'BCG vaccination', without any other filter, showed that skin manifestations like subcutaneous nodules, rash, ulcers and erythema in SCID patients with disseminated BCG have been described.…”
mentioning
confidence: 99%